Komunikacijski vidiki posegov v okolje - pomen analize socialnega okolja - Pek Drapal, Darinka (Teorija in praksa, 1999)
Article analyses NIMBY syndrome in cases of environmental interventions. The fact, that in most cases NIMBY syndrome is a result of communication incompetence of investors and project leaders of such interventions in local environment, is discussed. NIMBY syndrome is strongly related to the risk perception of local community. Risk perception is not only affected by the level of the technological and science development and with related trust in to the technological safety of the project, but much more by the social and psychological effects of the environmental intervention. If one should achieve efficient environmental intervention, social and psychological analysis of the local environment, that form the concept of social acceptability, should be performed beforehand or at least in time with technical studies of the environment itself. Every intervention in the environment should be supported by the professional communication. The strategy of such communication should come from the thorough scan of the localcommunity and especially on the social and psychological aspects of such an intervention.
Keywords: družbeno komuniciranje; posegi v okolje; prostorska analiza; participacija; NIMBY sindrom; odnosi z javnostjo; strategija